2009
DOI: 10.1074/jbc.m807269200
|View full text |Cite
|
Sign up to set email alerts
|

Pen2 and Presenilin-1 Modulate the Dynamic Equilibrium of Presenilin-1 and Presenilin-2 γ-Secretase Complexes

Abstract: ␥-Secretase is known to play a pivotal role in the pathogenesis of Alzheimer disease through production of amyloidogenic A␤42 peptides. Early onset familial Alzheimer disease mutations in presenilin (PS), the catalytic core of ␥-secretase, invariably increase the A␤42:A␤40 ratio. However, the mechanism by which these mutations affect ␥-secretase complex formation and cleavage specificity is poorly understood. We show that our in vitro assay system recapitulates the effect of PS1 mutations on the A␤42:A␤40 rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 45 publications
3
79
0
Order By: Relevance
“…blue indicated CS-1 had little to no effect on cell viability up to 30 M. In addition, we found that CS-3 exhibited an identical inhibitory profile with a slightly increased EC 50 for A␤42 inhibition (approximately 5 M). Compound E inhibited the production of all 3 ␤-amyloid species with equal potency (Fig.…”
Section: Di-coumarin Compounds Are Selective Gsis In Cellsmentioning
confidence: 53%
See 1 more Smart Citation
“…blue indicated CS-1 had little to no effect on cell viability up to 30 M. In addition, we found that CS-3 exhibited an identical inhibitory profile with a slightly increased EC 50 for A␤42 inhibition (approximately 5 M). Compound E inhibited the production of all 3 ␤-amyloid species with equal potency (Fig.…”
Section: Di-coumarin Compounds Are Selective Gsis In Cellsmentioning
confidence: 53%
“…The majority of mutations within each of these genes cause an increase in the ratio of A␤42 to A␤40 in biochemical, cellular, and animal models. Recent studies suggest that alteration of ␥-secretase complex dynamics and/or formation of ␥-secretase complexes with mutated components can affect the enzymatic cleavage specificity (30,31). Despite these advances in our understanding, little is known regarding the molecular mechanisms that control the specificity of ␥-secretase-mediated cleavage at the A␤40, A␤42, or Notch1 cleavage locations.…”
Section: Di-coumarin Inhibitors Alter the Sub-sites Of The ␥-Secretasmentioning
confidence: 99%
“…1B). All three probes only photolabel PS1-NTF but not PS1-CTF or other subunits (18,22,23,25). Membranes isolated from N2a cells stably expressing WT, M146L, E280A, FIGURE 1.…”
Section: Ps1 Mutationsmentioning
confidence: 99%
“…The PS1 M146V knock-in mice have been well characterized for memory formation and A␤ production (18,27,28). Membranes isolated from the M146V knock-in and PS1 WT mouse brain were labeled with the photoprobes JC8 and L646.…”
Section: Ps1 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation